Conceptions of Happiness Mediate the Relationship Between the Dark Triad and Well-Being - Joshanloo, Mohsen (Frontiers in Psychology, 2021)
This study explored the associations between the Dark Triad traits (i.e., Machiavellianism, psychopathy, and narcissism) and mental well-being in a Korean adult sample (N = 1,177). The role of the conceptions of happiness as mediators of these associations was also investigated. Eight conceptions of happiness (e.g., fragility of happiness and eudaimonism), 3 dimensions of hedonic well-being (e.g., life satisfaction), and 2 dimensions of eudaimonic well-being (e.g., psychological well-being) were included in the study. The results showed that Machiavellianism and psychopathy were negatively and narcissism was positively associated with well-being. The pattern of associations between the dark triad and conceptions of happiness showed that Machiavellianism and psychopathy were associated with valuing personal happiness but also considering it to be out of one's control, and to have negative consequences when achieved. People high on narcissism endorsed generally positive notions of happiness. Results showed that conceptions of happiness functioned as partial mediators in the relationships between the dark triad and well-being. Hence, it seems that the dark triad traits provide a context for the formation of certain beliefs surrounding the nature and value of well-being, which per se influence experienced levels of well-being.